UPAYA HUKUM TATA USAHA NEGARA OLEH NOTARIS YANG TIDAK DAPAT MENGAPLIKASIKAN HAK INGKAR NOTARIS AKIBAT PEMERIKSAAN MAJELIS KEHORMATAN NOTARIS YANG TIDAK SESUAI PROSEDUR (STUDI KASUS 13/G/2018/PTUN-TPI) - Pakpahan, Kartina; Fitriyani Pakpahan, Elvira; SIAHAAN, MARSEM PAHAM MARSAOR (Penerbit Lafadz Jaya, 2025)
This research aims to determine the Notary's responsibility for the deeds they create with the Notary's right of refusal. Additionally, it also examines the legal protection for Notaries who cannot exercise the Notary's right of refusal and analyzes the legal efforts made by Notaries in the context of Administrative Court proceedings. This research is normative in nature, using a Legislative Approach and a Case Approach in legal analysis. The legal sources involved in this research include primary and secondary legal materials. Based on the research findings, notaries have three responsibilities in carrying out their duties: civil, criminal, and administrative. Protection for Notaries who cannot exercise their right to refuse requires Notaries to disclose the contents of the deed and provide testimony in court. In the trial, it is known that the Notary Honorary Council (MKNW) can accompany the Notary during the examination process in front of the Investigator, Public Prosecutor, or Judge. What is meant by